Family History in Wills: Three Stories from Zadar - Nikolić, Zrinka (2006)
The wills of three families belonging to the highest circle of urban nobility in Zadar, Dalmatia – and intermarrying – de Grisogoni, de Matafari, and de Saladini) - are used as a source for studying family history – genealogy, kinship terminology, inheritance practice, and relationship among kinsmen. The main intention is to see what information about these issues we can gain from these sources in comparison with others – e.g. court records regarding disputes of inheritance, marital and dowry contracts, documents of property division, etc. This leads to the question of advantages and limitations of wills as a source for family history. Special emphasis is placed on changes in the treatment of descendants of different gender in the matters of family inheritance in the investigated period, which would be 1250-1400, in particular on comparing wills with normative sources. Given the fact that the three families belong to the same social milieu, the research is bound to reveal the existence of specific family policies in these matters.